Exploring Theologies of Money: Religious Leaders’ Use of Stewardship, Its Strengths, and Limitations - David P. King; Mark Sampson; Brad R. Fulton (Religions)
Questions of finance and economic models are vital for congregational leaders to consider, but they are too often overlooked in research and practice. While we argue that the explicit attention to budgets and balance sheets should be a focus of both congregational researchers and religious leaders, we would also argue that these topics are embedded in congregational life as practices and cultures of giving that are likewise rooted in theologies of money. To examine the theologies of money religious leaders rely on in shaping their views of receiving, managing, and spending resources, our study analyzes the qualitative data of 82 clergy interviews from the National Study of Congregations’ Economic Practices (NSCEP). We find that the language of “stewardship” continues to dominate, and we consider how this language has both shaped and masked congregations’ current and future engagement with money matters.